The impact of eLearning tools on the interprofessional learning experience in a first year foundations health unit - Bathgate, Katherine; Harris, Courtenay (Curtin University, 2012)
Foundations for Professional Health Practice 100 is a first year first semester unit that was developed for the Faculty of Health Sciences’ interprofessional common first year. To investigate the effectiveness of eLearning tools to assist the students in meeting two of the unit learning outcomes a cross sectional survey was undertaken. Results of the survey demonstrated that most eLearning tools (eg. Blackboard quizzes, wiki, Elluminate Live!, iPortfolio, Turnitin, and vodcasts) were effective in enabling students to achieve one or more of the course learning outcomes. These results show the value of using eLearning tools in first year tertiary courses to enhance student engagement and academic progress.